An Investigation Of How Faculty Learn To Teach At A Distance With Technology: Their Strategies For Solving The Problem - Rebecca D. Armstrong (Adult Education Research Conference, 1999)
This exploratory, qualitative research study sought to understand--from the faculty members' viewpoint--how they went about learning to teach at a distance with technology when not required to attend training. Findings point toward the importance of institutional context and indicate that some developmental process is occurring.